Green's Condition and Green-Kehayopulu Relations on $le$-Ternary Semigroups (Journal of Informatics and Mathematical Sciences, 2013)
We introduce the concept of the Green-Kehayopulu relations in $le$-ternary semigroups mimics the definition of the Green-Kehayopulu relations in $le$-semigroups that was introduced in 2002 by Petro and Pasku [3] and investigate the Green-Kehayopulu relations in $le$-ternary semigroups.
Keywords: $le$-semigroup; $le$-ternary semigroup; Green's condition; Green-Kehayopulu relation